Profil studenckiej rekreacji ruchowej na podstawie wybranych pomiarów sprawności fizycznej na przykładzie Uniwersytetu Kazimierza Wielkiego - Antkowiak, Magdalena; Engler, Maria; Drumińska, Ewelina; Wilczyńska, Sylwia; Stępniak, Robert; Pabianek, Łukasz (Journal of Education, Health and Sport, 2015)
Antkowiak Magdalena, Engler Maria, Drumińska Ewelina, Wilczyńska Sylwia, Stępniak Robert, Pabianek Łukasz. Profil studenckiej rekreacji ruchowej na podstawie wybranych pomiarów sprawności fizycznej na przykładzie Uniwersytetu Kazimierza Wielkiego = The students recreational profile - based on chosen parameters of physical fitness on the example of the Kazimierz Wielki University. Journal of Education, Health and Sport. 2015;5(8):326-336. ISSN 2391-8306. DOI 10.5281/zenodo.28967 http://dx.doi.org/10.5281/zenodo.28967 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A326-336 https://pbn.nauka.gov.pl/works/611599 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-e843f956-2ad8-4fef-857b-6e33b1dde738 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 21.08.2015. Profil studenckiej rekreacji ruchowej na podstawie wybranych pomiarów sprawności fizycznej na przykładzie Uniwersytetu Kazimierza Wielkiego The students recreational profile - based on chosen parameters of physical fitness on the example of the Kazimierz Wielki University Antkowiak Magdalena1, Engler Maria1, Drumińska Ewelina1, Wilczyńska Sylwia1, Stępniak Robert2, Pabianek Łukasz2 1 Sekcja Kultury Fizycznej, Koło Naukowe „Wykona” Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska 2 Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Corresponding autor: Stępniak Robert Ph.D Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, ul. Sportowa 2, 85-091 Bydgoszcz Polska email: <robi1969@wp.pl> Słowa kluczowe: rekreacja ruchowa, studenci, sprawność ogólna. Keywords: physical recreation, students, physical fitness. Streszczenie Cel: Jednym z problemów młodego pokolenie polskiego społeczeństwa rzutującym w przyszłości na stan zdrowia jest niska aktywnością fizyczną. Dotyczy to również młodzieży studenckiej, która poza obowiązkowym WF-em w niewielkim stopniu podejmuje dodatkowe ćwiczenia fizyczne. W prezentowanych badaniach sprawdzono sprawność fizyczną studentów Uniwersytetu Kazimierza Wielkiego w wybranych sekcjach sportowych i spróbowano stworzyć profil studenckiej rekreacji sportowej w oparciu o uzyskane wyniki. Materiał i metody: Badania sprawności ogólnej, wskaźnika BMI oraz zawartości tkanki tłuszczowej przeprowadzono w latach 2013/2015, na mężczyznach trenujących rekreacyjnie koszykówkę, pikę nożną i judo, a wyniki porównano z grupą osób nie ćwiczących rekreacji ruchowej. Materiał opracowano używając programu Excell wersja 2007. Wyniki: Wykazano istotne różnice pomiędzy sprawnością fizyczną studentów trenujących w sekcjach sportowych, a studentami prowadzącymi osiadły tryb życia. Wykazano również istotne różnice w niektórych wynikach sprawności fizycznej, wskaźnika BMI, oraz ilości tkanki tłuszczowej, pomiędzy studentami ćwiczącymi różne formy rekreacji ruchowej. Wnioski: Aktywność fizyczna studentów realizowana w różny sposób poprawia sprawność fizyczną studentów w różny sposób, który można ułożyć w charakterystyczny profil studenckiej rekreacji ruchowej. Profil rekreacji sportowej może być właściwym wskaźnikiem zachęcającym do podejmowania określonej aktywności fizycznej studentów. Abstract Objective: One of the problems of the young generation of Polish youth affecting in the future on human health, is low physical activity. This also applies to student youth, which, apart from the obligatory PE take only a little part in recreational physical fitness. In the present study we tested physical fitness of students at the Kazimierz Wielki in selected sports sections and try to create a student profile sports recreation on the basis of the results obtained. Material and Methods: The study contained: physical fitness, BMI and body fat, were carried out in the years 2013/2015, for men recreational exercisers basketball, football and judo. The results were compared with a group of non-exercisers recreation. The material was developed using Excel 2007 version of the program. Results: It show the significant differences between the physical fitness of students training in sports sections, and students leading a settled life. It was also demonstrated significant differences in some of the results of physical fitness, BMI, and fat tissue, between students from various forms of physical recreation. Conclusions: The students physical activity performed in a variety of ways improve physical fitness which can be arranged in a characteristic profile of the student recreation. These profile of sports recreation may be appropriate indicator for certain encouraging to physical activity students.